2012
DOI: 10.2147/sccaa.s28500
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the application of stem cell therapy in cardiovascular diseases

Abstract: Throughout their lifetime, an individual may sustain many injuries and recover spontaneously over a period of time, without even realizing the injury in the first place. Wound healing occurs due to a proliferation of stem cells capable of restoring the injured tissue. The ability of adult stem cells to repair tissue is dependent upon the intrinsic ability of tissues to proliferate. The amazing capacity of embryonic stem cells to give rise to virtually any type of tissue has intensified the search for similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Although treatment trials have been successfully conducted that minimize the complications, they have failed to address the pathological events caused by radiotherapy. In recent years, stem cell therapies have been proposed as a treatment option for degenerative diseases and disorders, including myocardial infarction, vascular diseases, motor neuron diseases, and neurodegenerative diseases ( Sharma et al, 2012 ). Our previous clinical trial showed that mesenchymal stem cells are potentially safe and effective in treating degenerated retinas ( Gu et al, 2018 ; Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment trials have been successfully conducted that minimize the complications, they have failed to address the pathological events caused by radiotherapy. In recent years, stem cell therapies have been proposed as a treatment option for degenerative diseases and disorders, including myocardial infarction, vascular diseases, motor neuron diseases, and neurodegenerative diseases ( Sharma et al, 2012 ). Our previous clinical trial showed that mesenchymal stem cells are potentially safe and effective in treating degenerated retinas ( Gu et al, 2018 ; Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Application of stem cells to therapeutic devices and methods may lead to effective and rapid myocardium regeneration and eventually affect cardiovascular morbidity and mortality [44]. There are different types of stem cells such as embryonic stem cells, adult stem cells, and induced pluripotent stem cells for treatment of CVDs (Table 1).…”
Section: Cardiovascular Diseases and Stem Cellsmentioning
confidence: 99%
“…This cell population is called ESCs and follows irreversible process of differentiation to become specialized [44, 46]. ESCs have pluripotency, with the capacity of differentiation into approximately 210 different cell types, making them an up-and-coming stem cell source for cell-based tissue engineering [44]. ESCs can be differentiated into cardiomyocytes, endothelial cells, and vascular smooth muscle cells [17, 18, 47, 48].…”
Section: Cardiovascular Diseases and Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation